1991
DOI: 10.1021/ar00008a003
|View full text |Cite
|
Sign up to set email alerts
|

Calicheamicins: discovery, structure, chemistry, and interaction with DNA

Abstract: Section. His research Interests are focused on natural products chemistry, drug/DNA Interactions, and mechanisms of antibiotic activity. Donald B. Borders Is the Department Head for the Microbial Chemistry Department In the Medical Research Division of American Cyanamid. He was bom In 1932 In Logansport, IN. He received a B.S. (1954) and M.A. (1958) In chemistry from Indiana University and a Ph.D. (1963) In Organic Chemistry from the University of Illinois (with K. L. Rinehart). From 1962 to 1964 he was a rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
94
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(96 citation statements)
references
References 64 publications
0
94
0
2
Order By: Relevance
“…2): a strand break consisting of 3Ј-phosphoglycolate-and 5Ј-phosphate-ended DNA fragments and base propenal; or a ketoaldehyde abasic site and free base (15). Calicheamicin and bleomycin have been shown to cause 4Ј-hydrogen atom abstraction (15,19,20). Calicheamicin is an enediyne antibiotic that, when activated by thiols, forms a minor groove-specific diradical species that abstracts deoxyribose hydrogen atoms (15,20).…”
Section: Resultsmentioning
confidence: 99%
“…2): a strand break consisting of 3Ј-phosphoglycolate-and 5Ј-phosphate-ended DNA fragments and base propenal; or a ketoaldehyde abasic site and free base (15). Calicheamicin and bleomycin have been shown to cause 4Ј-hydrogen atom abstraction (15,19,20). Calicheamicin is an enediyne antibiotic that, when activated by thiols, forms a minor groove-specific diradical species that abstracts deoxyribose hydrogen atoms (15,20).…”
Section: Resultsmentioning
confidence: 99%
“…1; reviewed in refs. 22,[25][26][27]. In the present studies, we have employed an analog of calicheamicin ␥, calicheamicin Ø, in which the methyl trisulfide trigger has been replaced by a thioacetate group that undergoes hydrolysis in the absence of thiols (Fig.…”
mentioning
confidence: 99%
“…Recently, natural disaccharides and trisaccharides have attracted enormous attention. 3,4) A large number of oligosaccharides have been conjugated for new DNA-binding antitumor agents, 3) and specific ligands for cell-surface recognition 4) have been produced by chemical and enzymatic syntheses.We demonstrated that the reaction of D-glucose with cyclotriphosphate (P 3m ) afforded b-D-glucopyranosyl 1-triphosphate in good yield in a one-step process without protection of hydroxyl groups.5,6) Although D-glucose exists as an equilibrium mixture of a and b anomers under the reaction conditions, only b-D-glucopyranosyl 1-triphosphate was obtained stereoselectively. This method would be applicable to the phosphorylation of other monosaccharides.…”
mentioning
confidence: 99%
“…Recently, natural disaccharides and trisaccharides have attracted enormous attention. 3,4) A large number of oligosaccharides have been conjugated for new DNA-binding antitumor agents, 3) and specific ligands for cell-surface recognition 4) have been produced by chemical and enzymatic syntheses.…”
mentioning
confidence: 99%